PRAKTIK MENEMUKAN PASANGAN HIDUP MELALUI PEMANFAATAN SITUS BIRO JODOH ONLINE - Sholihah, Mar'atush (Indonesian Association of Islamic Family Law Lecturers, 2021)
This paper is intended to explain how to practice finding a spouse through the online matchmaking sites. The background of online matchmaking sites is based on full-time public behavior that requires both dynamic and time-consuming matchmaking sites. In addition, users are used to communicate, to find pleasure by following trends and even being used out of curiosity. This paper results from qualitative research on primary data sources: interviews of 3 pairs and secondary data of both articles and research that discuss the role of social exchange in the detailed and detailed use of online matchmaking sites. To see this role or function of writing used a sociological approach to the theory of social connection between berger and luckmann, where it forms at the external level, that is, a concentrated activity in which humans try to connect to their social environment to be stable. The research suggests that online dating users do not make both online and social media dating sites the primary choice in finding mates, but as introduction gates. In this study both online matchmaking and social media users of websites starting with introductions continue to the meeting and continue to agree on a serious marriage relationship. This comes after pressure from the surrounding circumstances and conditions. Questions raised from the environment that have left the users feeling bored and depressed. Thus, the practice of finding spouses through the use of both online matchmaking and social media sites in the study is demanding.